Antimicrobial peptides and Complement - Maximising the inflammatory response - Cordula M. Stover (Frontiers Research Topics, 2015)
Antimicrobial peptides and complement are distinct components of the innate immune defence. While antimicrobial peptides, after cleavage of a preproprotein, have the ability to insert directly in non host membranes, complement requires a sequential enzymatic activation in the fluid phase in order to produce a transmembrane membrane attack complex. Its insertion is controlled by membrane bound regulators. Deficiencies are described for both effectors and relate to increased susceptibility of infection. In addition, however, antimicrobial peptides and complement each influence the activity of inflammatory cells as recent data in the respective research areas shows. This series of articles draws together for the entities of antimicrobial peptides and complement a balance of contributions in the areas of evolution, roles, functions and preclinical applications. By comparing and contrasting antimicrobial peptides and complement, greater cross-disciplinary appreciation will be derived for their individual and overlapping spectra of activity, circumstances of activation and their general ability to more completely inform the inflammatory and cellular response.